Efficient and Selective Removal of Sevi and Asv Mixed Contaminants from Aqueous Media by Montmorillonite-Nanoscale Zero Valent Iron Nanocomposite - Rubio-Campos, M; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Elsevier B.V., 2021)
Nanoscale zero-valent iron (NZVI) and NZVI supported onto montmorillonite (NZVI-Mt) were synthetized and used in this study to remove SeVI and AsV from water in mono- and binary-adsorbate systems. The adsorption kinetics and isotherm data for SeVI and AsV were adequately described by the pseudo-second-order (PSO) (r2>0.94) and Freundlich (r2>0.93) equations. Results from scanning electron microscopy showed that the dimension of the NZVI immobilized on the Mt was smaller than pure NZVI. Using 0.05 g of adsorbent and an initial 200 mg L−1 AsV and SeVI concentration, the maximum adsorption capacity (qmax) and partition coefficient (PC) for AsV on NZVI-Mt in monocomponent system were 54.75 mg g-1 and 0.065 mg g-1·μM-1, which dropped respectively to 49.91 mg g-1 and 0.055 mg g-1·μM-1 under competitive system. For SeVI adsorption on NZVI-Mt in monocomponent system, qmax and PC were 28.63 mg g-1 and 0.024 mg g-1·μM-1, respectively. Values of qmax and PC were higher for NZVI-Mt than NZVI and montmorillonite, indicating that the nanocomposite contained greater adsorption sites for removing both oxyanions, but with a marked preference for AsV. Future research should evaluate the effect of different operational variables on the removal efficiency of both oxyanions by NZVI-Mt. © 2020 Elsevier B.V.